2021
DOI: 10.3389/fgene.2021.579393
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulations by lncRNA, miRNA, and ceRNA Under Grass-Fed and Grain-Fed Regimens in Angus Beef Cattle

Abstract: Beef cattle raised under grass-fed and grain-fed have many differences, including metabolic efficiency and meat quality. To investigate these two regimens' intrinsic influence on beef cattle, we used high-throughput sequencing and metabolomics analyses to explore differentially expressed genes (DEGs) and metabolimic networks in the liver. A total of 200 DEGs, 76 differentially expressed miRNAs (DEmiRNAs), and two differentially expressed lncRNAs (DElncRNAs) were detected between regimen groups. Metabolic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…This is also consistent with our observation that greater amounts of G6P were detected in the muscle of FL cattle, which reflects more glucose availability in the muscle tissue, reflecting the differences in dietary intake, where animals finished in the feedlot had greater soluble carbohydrate intakes and consequently greater liver gluconeogenesis. Similarly, Jia et al [ 13 ], studying blood and liver transcriptomic and metabolomic of grass and grain-fed cattle, reported that grass feeding induces upregulation of those genes involved in fatty acid degradation and amino acid metabolism (catabolism) to meet the energy demands of the body. Carrillo et al [ 12 ] also reported that feeding changes specific gene expressions to support greater glucose metabolism, which is greater in the muscle of intensively fed cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also consistent with our observation that greater amounts of G6P were detected in the muscle of FL cattle, which reflects more glucose availability in the muscle tissue, reflecting the differences in dietary intake, where animals finished in the feedlot had greater soluble carbohydrate intakes and consequently greater liver gluconeogenesis. Similarly, Jia et al [ 13 ], studying blood and liver transcriptomic and metabolomic of grass and grain-fed cattle, reported that grass feeding induces upregulation of those genes involved in fatty acid degradation and amino acid metabolism (catabolism) to meet the energy demands of the body. Carrillo et al [ 12 ] also reported that feeding changes specific gene expressions to support greater glucose metabolism, which is greater in the muscle of intensively fed cattle.…”
Section: Discussionmentioning
confidence: 99%
“…This is not particularly surprising given changes in nutritional status and(or) environmental stimuli alter gene expression and elicit a whole host of changes in tissue metabolic pathways and subsequent metabolite abundances [ 4 , 5 , 6 , 7 , 8 , 9 ]. Even so, only a few studies have explored possible mechanisms undergirding the transcriptome and metabolome, namely in the rumen [ 10 ], spleen [ 11 ], muscle [ 12 ], and, more recently, in the liver and blood [ 13 ]. However, the molecular mechanisms responsible for inducing changes in meat quality parameters between these two highly competing production paradigms, where diet and growth rate can be quite diverse, have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of the liver in protein metabolism, differences in liver content and function may influence the nutrition composition of the meat later consumed by humans. In the grass-fed and grain-finished cattle, the altered gene expression was mainly responsible for lowering intramuscular fat, cholesterol, and yellow carcass-fat meat in grass-fed cattle and hence altered the nutrition composition of beef ( 10 ). However, the implications of consuming grass versus grain-finished beef, lamb, and PBMAs on the nutrition composition of the test meals and the resultant amino acid (AA) profile post–human consumption are, in theory, very important, but the clinical relevance is equally so.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively, the involvement of ceRNA in energy metabolism in metabolic diseases has been less reported. A study showed possible energy metabolic regulation by ceRNA under grassfed and grain-fed regimens in angus beef cattle (56). Another research indicates that ANRIL improves the mitochondrial function of hepatocellular carcinoma by regulating the miR-199a-5p/ARL2 axis (57).…”
Section: Discussionmentioning
confidence: 99%